ANALISIS FAKTOR PENERAPAN E-COMMERCE SEBAGAI RINTISAN MINAT BERWIRAUSAHA : Studi Kasus Pada Mahasiswa Riset Pemasaran Universitas Buddhi Dharma - Vandi Dwi Putra; Sonny Santosa; Rini Novianti (Universitas Bina Bangsa, 2022)
The pandemic period encourage the application of digitalization in the marketing field, the application of marketing culture is currently supported by e-commerce. On the other hand, students who should be in the potential group have been able to take advantage of this moment to develop creativity that results in innovation, at least as a first step as an effort to participate in and develop an interest in entrepreneurship. The purpose of this study is to analyze what factors are the pioneers of interest in entrepreneurship in marketing research students at the Faculty of Business, Buddhi Dharma University. As part of the “small research” activity, the researcher used a survey method and was included in the descriptive statistics group. The population taken was all students who took marketing courses in the odd year 2022/2023 which opened 40, thus the researchers took the entire population as a sample in this study. The analysis technique uses factor analysis. The results of this study indicate that personality and self-motivation factors are the dominant factors in the interest in entrepreneurship among students